2022
DOI: 10.3390/nu14112237
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profile of Different Dietary Patterns and Their Association with Frailty Index in Community-Dwelling Older Men and Women

Abstract: Diet quality has been associated with slower rates of aging; however, the mechanisms underlying the role of a healthy diet in aging are not fully understood. To address this question, we aimed to identify plasma metabolomic biomarkers of dietary patterns and explored whether these metabolites mediate the relationship between diet and healthy aging, as assessed by the frailty index (FI) in 806 participants of the Baltimore Longitudinal Study of Aging. Adherence to different dietary patterns was evaluated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Second, we estimated the associations between dietary patterns (in continuous variable) and 168 metabolites (log-transformed and then z -standardized) using multivariable linear regression adjusting for covariates in the aforementioned Model 2, eGFR 8 and the use of lipid-lowering drugs. 46 All yielded P values were corrected for false discovery rate (FDR) using Bonferroni corrections.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, we estimated the associations between dietary patterns (in continuous variable) and 168 metabolites (log-transformed and then z -standardized) using multivariable linear regression adjusting for covariates in the aforementioned Model 2, eGFR 8 and the use of lipid-lowering drugs. 46 All yielded P values were corrected for false discovery rate (FDR) using Bonferroni corrections.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary patterns reflect the overall diet quality through the combination and frequency of food consumption. 7 To date, several studies have shown significant positive associations between multiple healthy dietary patterns and frailty, [8][9][10][11][12][13][14] while there are also studies suggesting no associations. 15,16 Moreover, whether and to what extent the recommended food score (RFS), an important dietary pattern, is associated with frailty remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding determinants of individual variation in dietary responses and modeling such variations is challenging but could also improve the understanding of how specific foods affect key metabolites and their effects on disease risk factors. Important steps have already been taken [96][97][98][99] and more are currently ongoing. Interdisciplinary collaborations between experts in nutrition, medicine, and bioinformatics incorporating various omics and computational modeling-for example, machine learning and analysis of big data-are necessary to accomplish this task.…”
Section: Future Perspectivesmentioning
confidence: 99%